Disponibilidade e satisfação com o suporte social às pessoas com AIDS - Durgante, Vania Lucia (2012)
It is a transversal, descriptive and quantitative study developed to measure the social support and the satisfaction of patients with AIDS who are being treated with anti-retroviral medicine. The research was carried out at the University Hospital of Santa Maria, Rio Grande do Sul state, with a sample of 117 users registered at the Medicament Providing Unit of HIV/AIDS. The data were collected by means of a research protocol divided into two parts: a social-demographic questionnaire on health and the Social Support Scale. It was taken from February to April 2001, after signing the Free and Aware Agreement Term. For the storing and organization of information, it was built a data bank in the program Excel (Office 2007). After that, they were analyzed statistically with the help of software Statistical Package for the Social Sciences. The scale internal consistency was evaluated by Cronbach s Alpha Coefficient, which attested the certainty of the instrument measure (0.93). Dispersion and central tendency measures were used for the analysis and presentation of the outcomes. Mann Whitney and Kruskal-Wallis tests were used for the comparison among the interest variants and the scale dimension. Spearman correlation was used to assess the relation between the availability and satisfaction of the social support. It was identified 53.1% of male users, single and separated (49.7%), catholic (55.4%), mean age of 42.08 years (±10.04), concluded fundamental school, (39.5%) earned from one to three minimum wages (40.7%) and are active workers (45.2%). In the treatment beginning, it was noticed CV of average value and very low CD4, by the time of data collection of undetectable Viral Charge and normal CD4. It was seen 55.9% of hospital admissions after the diagnosis, 41.8% of them know the diagnosis between 6 and 10 years old and 61.5% have the treatment between one and six years of age. The most common support received was the emotional one and this support came from the family members. It is concluded that the social-demographic and health variables influenced the availability and satisfaction of the social support and in joining TARV . The most accepted social support was the emotional one and the support sources are from their families. The users evaluated the social support satisfaction as neither satisfied nor dissatisfied . The support received in concrete situations, which helps the health treatment, and the support, which makes them feel beloved, had the highest averages in the emotional and instrumental support, respectively. The financial support was the least common one. It should be highlighted the importance of this study for health professionals once it recognizes the social support as a mediator for the maintenance and promotion of health as well as the results of the social living as a factor to protect and give quality of life.